3D load estimation on a horizontal axis wind turbine using SPIV. (11th August 2013) - del Campo, V.; Ragni, D.; Micallef, D.; Akay, B.; Diez, F. J.; Simão Ferreira, C.
ABSTRACT The flow around the blade of a horizontal axis wind turbine wind tunnel model, operating at its optimal tip speed ratio in axial flow, has been investigated by means of stereoscopic particle image velocimetry (SPIV). The aim was to assess the possibility of measuring the loads impinged on the blade, using the acquired velocity field and its spatial derivatives. Thus, the three‐dimensional (3D) velocity field and the pressure distribution surrounding the blade, as well as the aerodynamic loads, responsible for thrust and torque, were obtained with a non‐intrusive method. The SPIV equipment was mounted on a traverse system and provided with phase‐locked velocity planes perpendicular to the blade axis, scanning the blade from the root to the tip, at a fixed azimuthal position. The obtained velocity fields were used to estimate the pressure distribution and the aerodynamic loads on each plane, using a 3D formulation. Finally, these results were compared and discussed with similar results obtained computationally with a panel method model, showing good consistency. In the future, the proposed methodology could be used to study relevant topics such as active load control techniques, rotational augmentation, dynamic stall phenomena and the aerodynamics of small wind turbines operating at low Re numbers, among others. The processed and averaged flow fields from the experimental SPIV data are made available online to the reader. See appendix for description of the files. Copyright © 2013 John Wiley & Sons, Ltd.